Women's experiences and acceptability of self-administered, home delivered, intravaginal 5-Fluorouracil cream for cervical precancer treatment in Kenya - Adewumi, Konyin; Kachoria, Aparna Ghosh; Adoyo, Everlyn; Rop, Mercy; Owaya, Antony; Tang, Jennifer H.; Rahangdale, Lisa; Mungo, Chemtai (Frontiers in Reproductive Health, 2025)
BackgroundInnovative strategies are essential to meet the World Health Organization's 90/70/90 cervical cancer elimination targets, aiming for 90% access to precancer treatment globally by 2030. In low-and middle-income countries (LMICs) where most cervical cancer cases occur, access to precancer treatment is severely limited. Scalable solutions like self-administered topical therapies can help close this gap. In a recent Phase I trial (ClinicalTrials.gov NCT05362955), we demonstrated safety and adherence to self-administered intravaginal 5% 5-Fluorouracil (5FU) cream as an adjuvant therapy for cervical precancer among women living with HIV (WLWH) in rural Kenya. To understand women's experiences with self-administered 5FU, we evaluated the acceptability of this intervention among trial participants.MethodsAll 12 participants from the Phase I trial completed a structured questionnaire and in-depth semi-structured interviews in their preferred language, focusing on their experiences with 5FU self-administration, challenges faced, and overall acceptability of the intervention, including whether they would use it again or recommend it to someone who needed it. Quantitative data were analyzed using descriptive statistics. In the qualitative study, acceptability was defined as “the perception that a given treatment is agreeable, palatable, or satisfactory.” A thematic analysis was conducted using five dimensions of acceptability: content, complexity, comfort, delivery, and credibility.ResultsThe mean age was 43.9 years (SD 4.4), and seven (58%) had primary education or less. While some participants reported feelings of uncertainty when they started using 5FU, at the end of the study, all 12 participants strongly agreed that the cream was safe and were confident they used it correctly. Most participants (91.7%) experienced no discomfort with the vaginal applicator, and most reported using tampons overnight after 5FU use, as recommended. Qualitative findings revealed that favorable perceptions of self-administered 5FU were driven by its ease of use, the discrete nature of the treatment, and the comfort of home application. The main challenges included correctly measuring the study drug, finding a private place at home to self-administer, and the need to use condoms during treatment. Compared to their previous ablation or excision treatments, participants found 5FU to be less painful, and all would prefer a self-administered treatment instead of a procedure if it were an option.ConclusionSelf-administered intravaginal 5FU as an adjuvant treatment for cervical precancer among women living with HIV in Kenya was highly acceptable. Randomized studies of 5FU and other topical therapies in LMICs are needed to evaluate their use in closing the current precancer treatment gaps in these settings.